The Structure of Amorphous and Deeply Supercooled Liquid Alumina - Shi, Caijuan; Alderman, Oliver L. G.; Berman, Diana; Du, Jincheng; Neuefeind, Joerg; Tamalonis, Anthony; Weber, J. K. Richard; You, Jinglin; Benmore, Chris J. (Frontiers in Materials, 2019)
Liquid Al2O3 has been supercooled more than 500 K below its melting point (Tm = 2327 K) using aerodynamic levitation and laser heating techniques. High energy synchrotron x-ray measurements were performed over a temperature range of 1817 ≤ T (K) ≤ 2700 and stroboscopic neutron diffraction at 1984 K and 2587 K. The diffraction patterns have been fitted with Empirical Potential Structure Refinement (EPSR) models and compared to classical molecular dynamics (MD) simulation results. Both sets of models show similar trends, indicating the presence of high populations of AlO4 and AlO5 polyhedral units predominantly linked by triply shared oxygen atoms. EPSR reveals that the mean Al–O coordination number changes linearly with temperature with nAlO = 4.41 – [1.25 × 10-4] (T – Tm), with a 2.5 Å cutoff. Both EPSR and MD simulations reveal a direction of the temperature dependence of the aluminate network structure which moves further away from the glass forming ideal i.e. towards nAlO = 3 during supercooling. Furthermore, we provide new experimental data and models for amorphous alumina grown by sequential infiltration synthesis of a polymer template. The amorphous solid form likely has a larger Al–O coordination number than the liquid, consistent with expectations for the hypothetical glass.